Dobutamine magnetic resonance imaging as a predictor of myocardial functional recovery after revascularisation. Issue 1 (1st January 2000) - Trent, R J; Waiter, G D; Hillis, G S; McKiddie, F I; Redpath, T W; Walton, S
Abstract : OBJECTIVE: To assess the use of dobutamine magnetic resonance imaging (MRI) as a preoperative predictor of myocardial functional recovery after revascularisation, comparing wall motion and radial wall thickening analyses by observer and semi-automated edge detection. PATIENTS: 25 men with multivessel coronary disease and resting wall motion abnormalities were studied with preoperative rest and stress MRI. MAIN OUTCOME MEASURES: Observer analysis for radial wall thickening was compared with a normal range, while wall motion analysis used a standard four point scale. Semi-automated analysis was performed using an edge detection algorithm. Segments displaying either improved or worsened thickening or motion with dobutamine were considered viable. Postoperative rest images were performed 3–6 months after coronary artery bypass grafting (CABG) for comparison. RESULTS: For observer analysis the values for sensitivity and specificity were 50% and 72% for wall motion, with respective values of 50% and 68% for thickening. With semi-automated edge detection the figures for motion were 60% and 73%, with corresponding values of 79% and 58% for thickening. Combining thickening and motion for the semi-automated method to describe any change in segmental function yielded a sensitivity of 71% and specificity of 70%. CONCLUSIONS: Dobutamine MRI is a reasonably good predictor of myocardial functional recovery after CABG. The use of semi-automated edge detection analysis improved results.